Wide dynamic range X-ray detector utilizing spectroscopic grade thallium bromide single crystal - Jiwon Seo; Seungho Song; Minhwan Park; Ajin Jo; Wonho Lee; Eunhye Kim; Younghak Kim; Mee Jang; Beomjun Park; Jung-Yeol Yeom (Nuclear Engineering and Technology, 2025)
This study aimed to evaluate the radiation response performance of thallium bromide (TlBr) across a wide range of dose rates. The TlBr crystal was purified and grown using a zone-refined purification furnace, and after completing 50 purification cycles, the single crystal was grown with a modified heater translation speed. The properties of the grown crystal were characterized using X-ray diffraction (XRD), current-voltage measurements, photoconductive measurement, and gamma-ray spectroscopy. X-ray performance was assessed under a wide dynamic range of dose rates, X-ray energies, and applied bias voltages. The results demonstrated a minimum detectable limit (MDL) of 130.19 nGy/s, confirming the detector's capability to respond to extremely low-dose X-ray exposure. Owing to its excellent material properties, X-ray measurements exhibited a high signal-to-noise ratio, enabling high-contrast X-ray imaging.